Out-of-Plane Strengthening of Unreinforced Masonry Walls by Glass Fiber-Reinforced Polyurea - Hye-Sook Jang; Jae-Hyoung An; Jun-Hyeok Song; Seung-Hwan Son; Yu-Sik Hong; Hee-Chang Eun (Civil Engineering Journal, 2022)
Fiber-reinforced polymer reinforcement or polyurea reinforcement techniques are applied to strengthen unreinforced masonry walls (UMWs). The purpose of this experimental study is to verify the out-of-plane reinforcing effect of sprayed glass fiber-reinforced polyurea (GFRPU), which is a composite elastomer made of polyurea and milled glass fibers on UMW. The out-of-plane strengths and ductile behaviors based on various coating shapes are compared in this study. An empirical formula to describe the degree of reinforcement on the out-of-plane strength of the UMW is derived based on the experimental results. It is observed that the peak load-carrying capacity, ductility, and energy absorption capacity gradually improve with an increase in the strengthening degree or area. Compared with the existing masonry wall reinforcement method, the GFRPU technique is a construction method that can help improve the safety performance along with ease of construction and economic efficiency. Doi: 10.28991/CEJ-2022-08-01-011 Full Text: PDF